Blended Learning in Increasing Learning Activeness of UNJA Student - Rasimin Rasimin; Affan Yusra (Jurnal Pendidikan dan Pembelajaran Kimia, 2021)
Abstract: Blended Learning in Increasing Learning  Activeness of UNJA Student . The research aims to: To improve the effectiveness of Blended Learning in improving learning activity in students UNJA. This type of research is quantitative research with Pre Experiment Draft research with model The One Group Pretest-Posttest. In this study drifting will focus on one group and then in the group at the initial stage will be given an initial test (pre-Test), then given the treatment and after the treatment will be carried out last Test (posttest), hereinafter from the comparison of the initial test (pre-Test) with the last Test (posttest). Analysis results proved that there is a blended learning (X) influence on the learning activity of tutoring and counseling (Y) students. These findings are obtained based on a series of data analysis that shows that the effectiveness of blended learning to the activation of students learned from the results of the difference Pree test of post-test amounted to 36.91%. The result of hypothetical test results that showed the effectiveness of blended learning to the activation of students learned the truth. It shows that more and more combinations of methods with props will influence the active student learning.Keywords: Blended Learning, learning activity.